Study on the Solidification and Heat Release Characteristics of Flexible Heat Storage Filled with PCM Composite - Tielei Yan; Gang Wang; Dong Zhang; Changxin Qi; Shuangshuang Zhang; Peiqing Li; Gaosheng Wei (Energies)
Phase change materials (PCMs) have significant potential for utilization due to their high energy storage density and excellent safety in energy storage. In this research, a flexible heat storage device using the stable supercooling of sodium acetate trihydrate composite is developed, enabling on-demand heat release through controlled solidification initiation. The solidification and heat release characteristics are investigated in experiments. The results indicate that the heat release characteristics of this heat storage device are closely linked to the crystallization process of the PCM. During the experiment, based on whether external intervention was needed for the solidification process, the PCM manifested two separate solidification modes—specifically, spontaneous self-solidification and triggered-solidification. Meanwhile, the heat release rates, temperature changes, and crystal morphologies were observed in the two solidification modes. Compared with spontaneous self-solidification, triggered-solidification achieved a higher peak surface temperature (53.6 °C vs. 46.2 °C) and reached 45 °C significantly faster (5 min vs. 15 min). Spontaneous self-solidification exhibited slower, uncontrollable heat release with dendritic crystals, while triggered-solidification provided rapid, controllable heat release with dense filamentous crystals. This controllable switching between modes offers key practical advantages, allowing the device to provide either rapid, high-power heat discharge or slower, sustained release as required by the application. According to the crystal solidification theory, the different supercooling degrees are the main reasons for the two solidification modes exhibiting different solidification characteristics. During solidification, the growth rate of SAT crystals exhibits substantial disparities across diverse experiments. In this research, the maximum axial growth rate is 2564 μm/s, and the maximum radial growth rate is 167 μm/s.